2021
DOI: 10.1177/15266028211030539
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Outcomes After Endovascular Abdominal Aortic Aneurysm Repair in Patients With Abnormal Findings on the First Postoperative Computed Tomography Angiography

Abstract: Purpose: Lifelong follow-up after endovascular abdominal aortic aneurysm repair (EVAR) is recommended due to a continued risk of complications, especially if the first postoperative imaging shows abnormal findings. We studied the long-term outcomes in patients with abnormalities on the first postoperative computed tomography angiography (CTA) following EVAR. Materials and Methods: This is a retrospective study of all consecutive patients who underwent elective EVAR for nonruptured abdominal aortic aneurysm (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The presence of a type II endoleak might have a negative impact in sac regression, 16 and even more, sac growth related to type IIEL might negatively impact the proximal seal [32][33][34] constituting a confounding factor when analyzing sac regression in HNA. In this series type II endoleaks were comparable for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a type II endoleak might have a negative impact in sac regression, 16 and even more, sac growth related to type IIEL might negatively impact the proximal seal [32][33][34] constituting a confounding factor when analyzing sac regression in HNA. In this series type II endoleaks were comparable for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency endovascular or surgical intervention is generally required. Computed tomography angiography (CTA) is the most commonly used effective means of postoperative examination and follow-up and can be used to conduct further intervention ( 10 , 11 ). However, we found that in some cases, CTA does not readily identify the intrinsic cause of IBO.…”
Section: Introductionmentioning
confidence: 99%